Augmented and virtual reality in retinal care: A systematic review of their role in training, surgery, and treatment - Erdag, Murat; Citirik, Mehmet; Dal, Ali (Elsevier Science Inc, 2025)
Augmented reality (AR) and virtual reality (VR) are game-changing technologies in retinal care, offering significant advancements in surgical training, diagnostic accuracy, and vision rehabilitation. We explore how AR/ VR is being used in surgical training, intraoperative guidance, and vision restoration, focusing on their impact on surgical proficiency, diagnostic precision, and the management of retinal diseases. We analyzed studies from the Web of Science Core Collection, adhering to PRISMA 2020 guidelines. We included randomized controlled trials (RCTs) and prospective cohort studies that examined AR/VR applications in retinal surgery, diagnosis, and rehabilitation. Bias was evaluated using RoB 2.0 for RCTs and ROBINS-I for observational studies. Ten studies met our criteria (3 RCTs and 7 prospective cohort studies) with 6-48 participants, focusing on AR/VR's role in surgical simulation, diagnostics, and vision rehabilitation. The Eyesi Surgical Simulator significantly improved surgical skills, reduced complications, and accelerated learning curves. AR-assisted diagnostics enhanced retinal disease detection, while VR rehabilitation programs helped improve contrast sensitivity and visual acuity; however, methodological differences between studies made direct comparisons difficult. AR/VR technologies have the potential to enhance retinal care by improving surgical safety, diagnostic precision, and rehabilitation outcomes. Despite these benefits, high costs, accessibility challenges, and a lack of standardization remain significant barriers. Integrating AR/VR into medical training and clinical practice is recommended, but larger, longterm studies are needed to validate their effectiveness.
Keywords: Augmented reality; Virtual reality; Retina; Surgical training; Ophthalmic education